Design Strategies for Aqueous Zinc Metal Batteries with High Zinc Utilization: From Metal Anodes to Anode-Free Structures - Zhang, Xianfu; Zhang, Long; Jia, Xinyuan; Song, Wen; Liu, Yongchang (Nano-Micro Letters, 2024)
Aqueous zinc metal batteries (AZMBs) are promising candidates for next-generation energy storage due to the excellent safety, environmental friendliness, natural abundance, high theoretical specific capacity, and low redox potential of zinc (Zn) metal. However, several issues such as dendrite formation, hydrogen evolution, corrosion, and passivation of Zn metal anodes cause irreversible loss of the active materials. To solve these issues, researchers often use large amounts of excess Zn to ensure a continuous supply of active materials for Zn anodes. This leads to the ultralow utilization of Zn anodes and squanders the high energy density of AZMBs. Herein, the design strategies for AZMBs with high Zn utilization are discussed in depth, from utilizing thinner Zn foils to constructing anode-free structures with theoretical Zn utilization of 100%, which provides comprehensive guidelines for further research. Representative methods for calculating the depth of discharge of Zn anodes with different structures are first summarized. The reasonable modification strategies of Zn foil anodes, current collectors with pre-deposited Zn, and anode-free aqueous Zn metal batteries (AF-AZMBs) to improve Zn utilization are then detailed. In particular, the working mechanism of AF-AZMBs is systematically introduced. Finally, the challenges and perspectives for constructing high-utilization Zn anodes are presented. Highlights: 1 Representative methods for calculating the depth of discharge of different Zn anodes are introduced. 2 Recent advances of aqueous Zn metal batteries with high Zn utilization are reviewed and categorized according to Zn anodes with different structures. 3 The working mechanism of anode-free aqueous Zn metal batteries is introduced in detail, and different modification strategies for anode-free aqueous Zn metal batteries are summarized.